Comparison of mortality prediction scores in elderly patients with ICD for heart failure with reduced ejection fraction. (14th October 2021) - Hayiroglu, M.I; Cinar, T; Cinier, G; Pay, L; Yumurtas, A.C; Tezen, O; Eren, S; Kolak, Z; Cetin, T; Ozcan, K.S; Turkkan, C; Ozbilgin, N; et al.
Abstract: Background: This investigation aimed to examine and compare the predictive value of MADIT-II, FADES, PACE and SHOCKED scores in predicting 1-year and long-term all-cause mortality in implantable cardioverter-defibrillator (ICD) implanted patients who were 75 years and over since there has been an area of uncertainty about the utility and usefulness of available risk scores in such cases. Methods: In this observational, retrospective study, ICD implanted 189 geriatric patients are divided into two groups according to the presence of long-term mortality in follow-up. The baseline characteristics and laboratory variables were compared between the groups. MADIT-II, FADES, PACE and SHOCKED scores were calculated at the time of ICD implantation. 1-year and long-term predictive value of these scores were compared by a receiver operating curve (ROC) analysis. Results: A ROC analysis showed that the best cut-off value of the MADIT-II score to predict 1-year mortality is 3 with 87% sensitivity and 74% specificity (AUC: 0.83; 95% CI: 0.73–0.94; p<0.001) and long-term mortality is 2 with 83% sensitivity and 43% specificity (AUC: 0.68; 95% CI: 0.60–0.76; p<0.001) The predictive value of MADIT-II was superior to FADES, PACE and SHOCKED scores in ICD implanted patients who are 75 years and over. Conclusion: MADIT-II score has a significant prognostic value compared to FADES, PACE and SHOCKED scores for the prediction of 1-year and long-term follow-up in geriatric patients implanted ICD for heart failure with reduced ejection fraction. Funding Acknowledgement: Type of funding sources: None.